Implant placement in conjunction with ridge split and expansion technique. (15th April 2019) - Kumar, I.; Singh, H.; Arora, S.S.; Singh, A.; Kumar, N.
Abstract: Aim: The aim of this study was to evaluate the efficacy of ridge split technique and expansion technique to analyse peri‐implant hard tissue changes following implant placement. Materials and methods: A prospective study was conducted at Swami Devi Dyal Hospital &Dental College, Panchkula, India, from 2015‐2017 on 10 patients, having at least 1–3 teeth missing, with a crestal width of at least 3 mm and an 8 mm apico‐coronal height (3 × 8 mm) from major anatomical structures. Results: Out of the 10 patients in whom the inclusion criteria met, six were male and four were female. Out of a total of 20 implants inserted, (13 implants in mandible and 7 in maxilla), healing was uneventful in all cases with no major complication. The mean bone width bucco‐lingually preoperatively was found to be 3.79 ± 0.36 mm and bucco‐lingual width recorded immediately after RST was found to be and 6.38 ± 0.51 mm. This difference in bone width was found to be significant ( P = 0.000). Also, a significant correlation was seen ( P = 0.003), further strengthening the results obtained. Conclusions: Within the limits of our study, placing implants with simultaneous ridge splitting can reduce the period of edentulism and reduces the duration of treatment with excellent results. Though it is an operator‐dependant technique and it cannot increase the vertical height of the ridge, still ridge split and expansion technique is the best method for augmentation and simultaneous implant insertion in case of narrow ridges with minimum morbidity and less treatment duration.